An improved de-embedding procedure for nanometer MOSFET small signal modeling. (November 2016) - Zhou, Ying; Yu, Panpan; Yan, Na; Gao, Jianjun
Abstract: An improved equivalent circuit model of the short test structure for nanometer metal-oxide-semiconductor field-effect transistor (MOSFET) device modeling is proposed in this paper. The skin effect of the feedlines is taken into account in the proposed model. The corresponding de-embedding method which is different from the conventional open/short de-embedding method is also presented here. A semi-analytical method has been used to determine the MOSFET small signal model parameters. Good agreement is obtained between the simulated and measured results for 90 nm MOSFETs in the frequency range of 1–40 GHz.